Oxygen uptake and resistance exercise methods: the use of blood flow restriction - Tarjino Junior, Adenilson (2018)
The literature has shown that a gap is identified regarding the acute effects of blood flow restriction training on aerobic variables. Objective: to analyze oxygen consumption (VO2) during and after two resistance training sessions: traditional high intensity and low intensity with blood flow restriction. Methods: After one-repetition maximum tests, eight male participants (25.7±3 years) completed the two experimental protocols, separated by 72 hours, in a randomized order: a) high intensity training at 80% of 1RM (HIRE) and b) low intensity training at 20% of 1RM combined with blood flow restriction (LIRE + BFR). Three sets of four exercises (bench press, squat, barbell bent-over row and deadlift) were performed. Oxygen consumption and excess post-exercise oxygen consumption were measured. Results: the data showed statistically significant differences between the traditional high intensity training and low intensity training with blood flow restriction, with higher values for traditional training sessions, except for the last five minutes of the excess post-exercise oxygen consumption. Oxygen consumption measured during training was higher (p = 0.001) for the HIRE (20.32 ± 1.46 mL∙kg-1∙min-1) compared to the LIRE + BFR (15.65 ± 1.14 mL∙kg-1∙min-1). Conclusion: Oxygen uptakes rates during and after the exercise sessions were higher for the high intensity training methodology. However, when taking into account the volume of training provided by both methods, these differences were attenuated. Level of Evidence III - Non-consecutive studies, or studies without consistently applied reference stand.